Politeness Strategies of Directive Utterance Used by the Host of Satu Jam Lebih Dekat Talk Show on TV One - Sumarni Sumarni; Zainuddin Zainuddin (LINGUISTIK TERAPAN, 2016)
This study deals with the politeness strategies of directive utterance used by the host of Satu Jam Lebih Dekat Talk Show on TV One. This study employs qualitative design which aims at describing the politeness strategy of directive utterance used by the host. The strategy of politeness is related to those proposed by Brown and Levinson (1987); Bald on record strategy, Positive politeness, Negative politeness, and Off-record strategy. Directive utterance is related to those proposed by Vanderveken (1990); there are 56 types of directive utterances. The subject is the host as the interviewer in three episodes who participated in this research. The results show that the host expresses her directive utterances in request, questions, interrogates, urge, invite, and cautions. The host applied the four types of politeness strategies to relate directive utterances as politeness strategies stated by Brown and Levinson they are (1) bald on record, (2) positive politeness, (3) negative politeness, (4) off record. The most type is question (30%) as positive politeness. It is caused by the host wants to give questions respects the H’s negative face want and will not (or will only minimally) interfere with the H’s freedom of action. Keywords: politeness strategies, directive utterances